Peran Kepala Desa Dalam Pemberdayaan Keluarga Untuk Mengatasi Risiko Stunting Pada Balita Di Desa Cinta Rakyat Kecamatan Merdeka Kabupaten Karo - Br Ginting, Ananda Sari (Universitas Muhammadiyah Sumatera Utara, 2024)
Community limitations in various sectors are a contributing factor to stunting in toddlers. The current situation in Cinta Rakyat Village shows that there is still a lack of information, knowledge and economy and community indifference to stunting. The purpose of this study was to determine the role of the village head in empowering families to overcome the risk of stunting in toddlers in Cinta Rakyat Village, Merdeka District, Karo Regency. The theory used in this research is empowerment theory, where family empowerment is the main focus of the government to achieve the goal of creating empowered and prosperous families. The method used in this research is a qualitative method with a total of 6 informants, namely the village head, KPM, 2 posyandu cadres and 2 families of toddlers with data collection techniques through interviews and document analysis. The data analysis technique in this study refers to 3 streams of activities namely data reduction, data presentation, and conclusion drawing. The results showed that: (1) the role of the village head in family empowerment, including (a) as a motivator, facilitator and mobilizer, (b) improving the family economy through waste banks, (c) providing sanitation in the form of latrines, (d) providing information (2) obstacles faced in the acceleration of stunting reduction program. Creating empowerment in the village certainly requires cooperation from various parties, especially the village head and the community. The result of this collaboration is that the family of toddlers has the ability to empower the family and there has been an increase in family welfare with the risk of stunting toddlers.